2022
DOI: 10.1101/2022.01.31.478441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peptide location fingerprinting identifies species- and tissue-conserved structural remodelling of proteins as a consequence of ageing and disease

Abstract: Extracellular matrix (ECM) in the intervertebral disc (IVD), lung and artery are thought to undergo the age-dependant accumulation of damage by chronic exposure to mechanisms such as reactive oxygen species, proteases and glycation. It is unknown whether this damage accumulation is species-dependant (via differing lifespans and hence cumulative exposures) or whether it can influence the progression of age-related diseases such as atherosclerosis. Peptide location fingerprinting (PLF) is a new proteomic analysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 137 publications
(234 reference statements)
0
2
0
Order By: Relevance
“…In this study we used cells from a single human donor as a source of ECM proteins. We have previously shown using PLF that, for many ECM proteins, their peptide fingerprint is remarkably well conserved between cells and tissues from different individuals and even between different species (Eckersley et al, 2020(Eckersley et al, , 2022(Eckersley et al, , 2023. However, it is also the case that, due to the statistical nature of PLF analyses, UVR-induced changes in lower abundance proteins may be missed in our current analysis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study we used cells from a single human donor as a source of ECM proteins. We have previously shown using PLF that, for many ECM proteins, their peptide fingerprint is remarkably well conserved between cells and tissues from different individuals and even between different species (Eckersley et al, 2020(Eckersley et al, , 2022(Eckersley et al, , 2023. However, it is also the case that, due to the statistical nature of PLF analyses, UVR-induced changes in lower abundance proteins may be missed in our current analysis.…”
Section: Discussionmentioning
confidence: 83%
“…However PLF did not detect statistically significant changes following high-UVR exposure (Figure 2G). We have previously shown that PLF is well-suited to detecting changes in peptide yield and hence fingerprint where control proteins (non-UV exposed or young) exhibit a conserved fingerprint and any induced changes (due to UVR exposure or ageing) are also conserved (Eckersley et al, 2022). However, where proteins are subject to extensive and potentially stochastic changes in structure and hence tryptic cleavage (as indicated by the aggregation and smearing observed in Figures 2A-C) the PLF technique may struggle to identify significant changes in peptide yield.…”
Section: Discussionmentioning
confidence: 99%